2019
DOI: 10.1111/andr.12690
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is not associated with reproductive parameters in young Spanish men

Abstract: Background Relatively low sperm count was reported among young Spanish men in 2013. Several potential culprits have been suggested as explanations for reported trends in sperm counts in Western men, including lifestyles. Although controversial, some studies suggest that semen parameters, such as low sperm motility or abnormal morphology, may be associated with low serum vitamin D levels. Objectives To evaluate associations between semen parameters and reproductive hormones and serum 25‐hydroxyvitamin D (25OHD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
3
5
1
Order By: Relevance
“…Results similar to ours were obtained by Rudnicka et al 28 , who showed no association between vitamin D levels and LH, FSH, TT, inhibin B, or estradiol levels (as well as semen parameters) in young men. In addition, Ramlau-Hansen et al 29 also found that LH, TT, and inhibin B levels were not significantly associated with vitamin D. Similarly, Lerchbaum et al 30 indicated that significantly elevated serum vitamin D levels in the subjects had no effect on changes in total testosterone levels in middle-aged men.…”
Section: Discussionsupporting
confidence: 92%
“…Results similar to ours were obtained by Rudnicka et al 28 , who showed no association between vitamin D levels and LH, FSH, TT, inhibin B, or estradiol levels (as well as semen parameters) in young men. In addition, Ramlau-Hansen et al 29 also found that LH, TT, and inhibin B levels were not significantly associated with vitamin D. Similarly, Lerchbaum et al 30 indicated that significantly elevated serum vitamin D levels in the subjects had no effect on changes in total testosterone levels in middle-aged men.…”
Section: Discussionsupporting
confidence: 92%
“…The vitamin D intake by our student population was lower than mentioned average intakes, but similar to the southern and eastern European countries 8 . There is a gap in the literature regarding vitamin D intake by university student population, and to the available, dietary vitamin D intake by our male students was almost the same as Spanish 20,21 and lower than Swedish 22 male university students. Vitamin D intake by our female students was the same as Spanish female university students 21 .…”
Section: University Students' Habits Concerning Daily Sunlight Exposurecontrasting
confidence: 65%
“…16,[26][27][28][29][30] In contrast, vitamin D status was not associated with serum testosterone in healthy younger men. 18,[31][32][33] In this RCT, vitamin D + calcium supplementation improved testosterone/LH ratio in vitamin D insufficient men, which is in accordance with a small RCT supplementing 4000 IU cholecalciferol or placebo to infertile men, which combined indicate that vitamin D rather than calcium increased testosterone/LH ratio. 34 Our results do not elucidate the mechanism behind the increased testosterone/LH ratio caused by vitamin D + calcium supplementation.…”
Section: Discussionsupporting
confidence: 87%